Balance and ankle muscle strength predict spatiotemporal gait parameters in individuals with diabetic peripheral neuropathy - Camargo, Marcela R. [UNESP]; Barela, José A. [UNESP]; Nozabieli, Andréa J. L. [UNESP]; Mantovani, Alessandra M. [UNESP]; Martinelli, Alessandra R. [UNESP]; Fregonesi, Cristina E. P. T. [UNESP] (Elsevier B. V., 2015)
The aims of this study were to evaluate aspects of balance, ankle muscle strength and spatiotemporal gait parameters in individuals with diabetic peripheral neuropathy (DPN) and verify whether deficits in spatiotemporal gait parameters were associated with ankle muscle strength and balance performance. Thirty individuals with DPN and 30 control individuals have participated. Spatiotemporal gait parameters were evaluated by measuring the time to walk a set distance during self-selected and maximal walking speeds. Functional mobility and balance performance were assessed using the Functional Reach and the Time Up and Go tests. Ankle isometric muscle strength was assessed with a handheld digital dynamometer. Analyses of variance were employed to verify possible differences between groups and conditions. Multiple linear regression analysis was employed to uncover possible predictors of gait deficits. Gait spatiotemporal, functional mobility, balance performance and ankle muscle strength were affected in individuals with DPN. The Time Up and Go test performance and ankle muscle isometric strength were associated to spatiotemporal gait changes, especially during maximal walking speed condition. Functional mobility and balance performance are damaged in DPN and balance performance and ankle muscle strength can be used to predict spatiotemporal gait parameters in individuals with DPN.
Keywords: Balance; Diabetes mellitus; Diabetic peripheral neuropathy; Gait; Muscle strength